Composite silicon-carbon material, preparation method and application thereof, and lithium ion battery

By using polymer nanospheres containing transition metals and carbon sphere precursors with carbon sources for heat treatment and chemical vapor deposition, the problems of low silicon load and poor conductivity of silicon carbon materials in the prior art are solved, and composite silicon carbon materials with high silicon load and excellent conductivity are achieved, and composite silicon carbon materials with high silicon load and excellent conductivity are suitable for negative electrode materials of lithium-ion batteries.

CN119503794AActive Publication Date: 2025-02-25SHANGHAI SHANSHAN NEW MATERIAL CO LTD

Patent Information

Application Number
CN202411763282.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-02-25
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

In the prior art, the silicon-carbon material obtained by porous carbon spheres prepared by the template method has a low silicon load and poor conductivity, and the preparation method is high and the steps are complicated.

Method used

The carbon sphere precursor with polymer nanospheres containing transition metals and carbon source is heat-treated, carbonization and activation treatment are carried out. Silicon and carbon are deposited by chemical vapor deposition method to remove transition metals, and composite silicon carbon materials with high silicon loading and excellent conductivity are prepared.

Benefits of technology

A composite silicon carbon material with high silicon load capacity and excellent conductivity is achieved, and is an anode material for lithium-ion batteries, with excellent capacity performance, cycle performance and first-time efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503794A_ABST
    Figure CN119503794A_ABST
Patent Text Reader

Abstract

The invention discloses a composite silicon carbon material, a preparation method and application thereof and a lithium ion battery, and the preparation method comprises the following steps: S1, carrying out heat treatment, carbonization treatment and activation treatment on a carbon sphere precursor to obtain a porous carbon sphere; the carbon sphere precursor comprises a carbon source and a polymer nanosphere containing transition metal; the transition metal-containing polymer nanosphere comprises a polymer nanosphere matrix and a transition metal coating layer, s2, performing silicon deposition on the porous carbon spheres by adopting first chemical vapor deposition to obtain a silicon carbon material precursor; s3, performing carbon deposition on the silicon carbon material precursor by adopting second chemical vapor deposition; and removing the transition metal to obtain the composite silicon-carbon material. The obtained composite silicon-carbon material is high in silicon loading capacity and excellent in stability and conductivity, the lithium ion battery adopting the composite silicon-carbon material is excellent in capacity performance, and excellent cycle performance and initial efficiency can be taken into account.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention provides a composite silicon-carbon material, a preparation method thereof, an application thereof and a lithium-ion battery. Background Art

[0002] Porous carbon materials are widely used in the fields of catalyst carriers, energy storage materials, separation materials, etc. due to their high specific surface area, high adsorption and other properties. Among them, spherical porous carbon has received widespread attention due to its regular structure and good stability. However, the traditional preparation method of spherical porous carbon often requires high-temperature treatment, which is costly, and the pore size and porosity of the obtained porous carbon are difficult to control. When applied to the technical field of preparing silicon-carbon materials, the cost is often high, and the electrical conductivity of silicon-carbon materials is poor and the silicon loading is low.

[0003] The existing solutions mainly involve introducing nickel metal into porous carbon through chemical vapor deposition, sol-gel method and other methods, and using silicon dioxide as a template to make pores in the carbon source to obtain spherical porous carbon, thereby improving the conductivity and silicon loading of silicon-carbon materials. However, these methods usually require high-temperature treatment, complicated steps, and the obtained nickel metal is unevenly distributed in the porous carbon, which may affect the performance of the final nickel-doped spherical porous carbon, and the conductivity and silicon loading of the silicon-carbon material are still poor. Therefore, how to prepare spherical porous carbon with good performance under low-cost, simple and easy conditions, and then obtain silicon-carbon materials with good conductivity and high silicon loading, is an important challenge facing current technology. Summary of the invention

[0004] In order to solve the defects of low silicon loading and poor conductivity in the silicon-carbon material obtained from porous carbon spheres prepared by the template method in the prior art, the present invention provides a composite silicon-carbon material and its preparation method, application and lithium-ion battery. The obtained composite silicon-carbon material has a high silicon loading and excellent stability and conductivity. The lithium-ion battery using the composite silicon-carbon material has excellent capacity performance and can take into account excellent cycle performance and first efficiency.

[0005] To achieve the above objectives, the present invention adopts the following technical solutions.

[0006] The present invention provides a method for preparing a composite silicon-carbon material, which comprises the following steps:

[0007] S1, heat-treating, carbonizing and activating a carbon sphere precursor to obtain porous carbon spheres; the carbon sphere precursor comprises a carbon source and a transition metal-containing polymer nanosphere; the transition metal-containing polymer nanosphere comprises a polymer nanosphere matrix and a transition metal coating layer;

[0008] S2, depositing silicon on the porous carbon spheres using a first chemical vapor deposition method to obtain a silicon-carbon material precursor;

[0009] S3, using a second chemical vapor deposition to deposit carbon on the silicon-carbon material precursor; removing the transition metal to obtain a composite silicon-carbon material.

[0010] In some embodiments, in step S1, the carbon source is preferably a phenolic resin. The phenolic resin may be a thermosetting phenolic resin or a thermoplastic phenolic resin. The thermoplastic phenolic resin is preferably a linear phenolic resin, which needs to be used in combination with a curing agent.

[0011] Preferably, the softening point of the phenolic resin is 95-105°C.

[0012] In some preferred embodiments, the carbon source is phenolic resin, and the method for preparing the carbon sphere precursor comprises the following steps:

[0013] S0. Adding a carbon sphere precursor mixture into a dispersant aqueous solution, and subjecting the mixture to a curing reaction, to obtain a carbon sphere precursor; wherein the carbon sphere precursor mixture comprises a phenolic resin, a curing agent, a solvent and polymer nanospheres containing a transition metal; and a transition metal coating layer is disposed on the surface of the polymer nanospheres.

[0014] The curing agent may be a curing agent conventionally used in the art, such as one or more of hexamethylenetetramine, polyoxymethylene, A-stage thermosetting phenolic resin and aniline.

[0015] The mass ratio of the phenolic resin to the curing agent is preferably (15-20):1, for example, 16.7:1.

[0016] Wherein, the mass ratio of the phenolic resin to the transition metal-containing polymer nanospheres is preferably (20-40):1.

[0017] The curing reaction temperature is preferably 95-130° C., such as 115° C.; preferably, the curing reaction time is 1-2 h.

[0018] Wherein, the curing reaction preferably further includes filtering and drying.

[0019] Preferably, the adding is performed while stirring; the stirring speed is preferably 300-500 r / min, for example 400 r / min.

[0020] The dispersant in the aqueous dispersant solution may be a dispersant commonly used in the art, preferably one or more of polyvinyl alcohol, polyvinyl pyrrolidone (PVP), polyethylene glycol and sodium dodecyl sulfate, such as polyvinyl alcohol.

[0021] The mass fraction of the dispersant aqueous solution is preferably 0.8%-2%, for example 1.4%, where the percentage is the mass percentage of the dispersant in the dispersant aqueous solution to the mass percentage of the dispersant aqueous solution.

[0022] The method for preparing the carbon sphere precursor mixture preferably comprises the following steps:

[0023] A phenolic resin, a curing agent and a solvent are mixed to obtain a mixed solution, and polymer nanospheres are added to the mixed solution to obtain a carbon sphere precursor mixture.

[0024] The solvent may be a conventional solvent in the art, such as ethanol and / or methanol. The mass ratio of the phenolic resin to the solvent is preferably (0.4-1):1, such as 0.67:1.

[0025] In step S1, the polymer nanosphere matrix is ​​preferably polyethylene nanosphere and / or polystyrene (PS) nanosphere.

[0026] In step S1, the transition metal in the transition metal coating layer preferably includes one or more of nickel, copper, tin, palladium and iron, and more preferably includes one or more of nickel, tin and palladium.

[0027] In step S1, the preparation method of the transition metal-containing polymer nanospheres is preferably a chemical plating method, and the chemical plating method preferably includes the following steps: mixing the polymer nanosphere matrix and the transition metal plating solution, centrifuging, washing, and drying to obtain the polymer nanospheres.

[0028] Wherein, the pH value of the transition metal plating solution is preferably 6-10, for example, 8 or 9.

[0029] Wherein, the particle size of the polymer nanosphere matrix is ​​preferably 20-200 nm, for example, 200 nm.

[0030] The mixing is preferably carried out by ultrasound. Preferably, the ultrasound time is 0.5-1.5 hours, for example, 1 hour.

[0031] The drying temperature is preferably 40-60°C, for example 50°C.

[0032] In some embodiments, the transition metal plating solution preferably includes the following components: transition metal salt 20-60 g / L, for example, 40 g / L; NaH2PO2 20-80 g / L, for example, 60 g / L; Na3C6H5O7·2H2O 10-100 g / L, for example, 60 g / L; NH4Cl 10-50 g / L, for example, 30 g / L; and a strong base compound, for example, NaOH.

[0033] In some embodiments, the content of the strong base compound in the transition metal plating solution is 10%-15%, where the percentage is the mass percentage of the total mass of the chemical plating solution.

[0034] In some embodiments, the transition metal salt in the chemical plating solution is preferably one or more of nickel sulfate, nickel chloride, copper sulfate, stannous chloride, palladium chloride and ferric chloride.

[0035] In some embodiments, before mixing the polymer nanosphere matrix and the transition metal plating solution, the polymer nanosphere matrix is ​​further subjected to a pretreatment, which preferably includes a roughening treatment and a sensitization and activation treatment.

[0036] Wherein, the roughening treatment preferably includes the following steps:

[0037] Concentrated sulfuric acid is slowly added into water to form a sulfuric acid aqueous solution, potassium dichromate is then added and mixed, and then the nanosphere matrix is ​​added and ultrasonic treatment is performed.

[0038] In some embodiments, the temperature of the ultrasonic treatment is preferably 40-60°C, for example 50°C.

[0039] In some embodiments, the ultrasonic treatment time is preferably 30-90 min, for example 60 min.

[0040] In some embodiments, the concentration of sulfuric acid in the aqueous sulfuric acid solution is preferably 10-30%, where the percentage is the mass percentage of the aqueous sulfuric acid solution.

[0041] In some embodiments, the molar ratio of sulfuric acid to potassium dichromate is preferably (1-10):1.

[0042] Wherein, the sensitization activation treatment preferably includes the following steps:

[0043] The polymer nanosphere matrix that has been roughened is dispersed in water to obtain a polymer nanosphere matrix mixture, and stannous chloride and palladium chloride are respectively added to the polymer nanosphere matrix mixture, and ultrasonic treatment is performed.

[0044] In some embodiments, the temperature of the ultrasonic treatment is preferably 40-60°C, such as 45°C.

[0045] In some embodiments, the ultrasonic treatment time is preferably 0.5-1.5 h, for example 1 h.

[0046] In some embodiments, the concentration of the polymer nanosphere matrix in the polymer nanosphere matrix mixture is 10%-30%, where the percentage is the mass percentage of the resin microsphere mixture.

[0047] In some embodiments, the mass ratio of the polymer nanosphere matrix, stannous chloride and palladium chloride is 100:(2-5):(0.05-0.1).

[0048] In step S1, the temperature of the heat treatment is preferably 200-400°C, more preferably 250-350°C, more preferably 280-320°C, for example 300°C.

[0049] In step S1, the heat treatment time is preferably 1-3 h, for example 2 h.

[0050] In step S1, the heating rate to the heat treatment temperature is preferably 1-5°C / min, for example 5°C / min.

[0051] In step S1, the temperature of the carbonization treatment is preferably 700-900°C, more preferably 750-850°C, for example 800°C.

[0052] In step S1, the carbonization treatment time is preferably 2-4 hours, for example, 2 hours.

[0053] In step S1, the heating rate to the temperature of the carbonization treatment is preferably 1-5°C / min, for example, 2°C / min.

[0054] In step S1, the atmosphere of the carbonization treatment is preferably an inert atmosphere, which may be nitrogen or an inert gas (such as argon). The inert atmosphere in the present invention refers to a gas environment that does not chemically react with raw materials or other substances, and is not equivalent to an inert gas, such as nitrogen.

[0055] In step S1, the activation treatment is preferably alkali activation or gas activation; wherein the gas activation is preferably carbon dioxide activation or water vapor activation.

[0056] In some preferred embodiments, in step S1, the activation treatment is carbon dioxide activation.

[0057] The activation temperature of carbon dioxide is preferably 850-1000°C, more preferably 900-1000°C, and further more preferably 900-950°C; the heating rate to the activation temperature of carbon dioxide is preferably 1-5°C / min, for example 1°C / min.

[0058] The activation time of carbon dioxide is preferably 2-6 h, for example 3 h.

[0059] In step S1, the specific surface area of ​​the porous carbon sphere is preferably 1500-2500 m 2 / g, for example, 1523 m2 / g, 1532 m 2 / g, 1583 m 2 / g, 1624 m 2 / g, 1625 m 2 / g, 1642 m 2 / g, 1682 m 2 / g, 1683 m 2 / g or 1823 m 2 / g.

[0060] In step S1, the Dv50 particle size of the porous carbon spheres is preferably 9-12 μm, for example, 9.8 μm, 10.3 μm, 10.4 μm, 10.5 μm, 10.7 μm, 10.8 μm or 11.1 μm.

[0061] In step S1, the pore volume of the porous carbon sphere is preferably 0.6-1.0 cm 3 / g, more preferably 0.7-0.95 cm 3 / g, for example, 0.74 cm 3 / g, 0.79 cm 3 / g, 0.81 cm 3 / g, 0.83 cm 3 / g, 0.84 cm 3 / g, 0.85 cm 3 / g or 0.86cm 3 / g.

[0062] In step S1, the proportion of micropores in the porous carbon sphere is preferably 58%-98%, more preferably 58%-74%, for example 64%, 66%, 67%, 68% or 70%, where the percentage is the proportion of the volume of the micropores to the total pore volume of the porous carbon sphere. The micropores refer to pores with a pore size of less than 2 nm.

[0063] In step S1, the proportion of mesopores in the porous carbon sphere is preferably 10%-32%, more preferably 20%-30%, for example 24%, 25%, 26%, 27% or 29%, where the percentage is the proportion of the volume of the mesopores to the total pore volume of the porous carbon sphere. The mesopores refer to pores with a pore size of 2-50 nm.

[0064] In step S1, the proportion of macropores in the porous carbon sphere is preferably 1%-15%, for example, 6%, 7%, 8%, 9% or 10%, where the percentage is the proportion of the volume of the macropores to the total pore volume of the porous carbon sphere. The macropores refer to pores with a pore diameter greater than 50 nm.

[0065] In step S1, the carbon content in the porous carbon sphere is preferably 85%-94%, more preferably 88%-92%. The carbon content in the porous carbon sphere is, for example, 88.6%, 90.3%, 90.8%, 91.6%, 92.4%, 92.9%, 93.3% or 93.6%, where the percentage is the mass percentage of the total mass of the porous carbon sphere.

[0066] In step S1, the content of oxygen in the porous carbon sphere is preferably 1%-8%, more preferably 3%-6%. The content of oxygen in the porous carbon sphere is, for example, 1.2%, 1.8%, 2.8%, 4.1%, 4.2%, 4.3%, 4.7%, 4.8% or 7.7%, where the percentage is the mass percentage of the total mass of the porous carbon sphere.

[0067] In step S1, the content of transition metal elements in the porous carbon sphere is preferably 1%-6%, and the percentage is the mass percentage of the total mass of the porous carbon sphere. When the transition metal elements in the porous carbon sphere include nickel, the content of nickel is preferably 1.5%-5.5%, for example, 2.8%, 3.5%, 4.2%, 4.3%, 4.8%, 5.2%, 5.3% or 5.4%, and the percentage is the mass percentage of the total mass of the porous carbon sphere.

[0068] In step S2, the silicon source for the first chemical vapor deposition is preferably organic silane, more preferably one or more of methylsilane, disilane and chlorosilane, for example, methylsilane.

[0069] The flow rate of the silicon source is preferably 200-300 cc / min, for example 250 cc / min.

[0070] In step S2, the temperature of the first chemical vapor deposition is preferably 500-700°C, for example 600°C.

[0071] In step S2, the time of the first chemical vapor deposition is preferably 2-6 h, for example 3 h.

[0072] In step S2, the heating rate of heating to the first chemical vapor deposition temperature is preferably 1-5°C / min, for example, 3°C / min.

[0073] In step S2, the atmosphere of the first chemical vapor deposition is preferably an inert atmosphere. The inert atmosphere may be nitrogen or an inert gas (such as argon). The inert atmosphere in the present invention refers to a gas environment that does not chemically react with raw materials or other substances, and is not equivalent to an inert gas, such as nitrogen.

[0074] The flow rate of the atmosphere is preferably 450-550 cc / min, for example, 500 cc / min.

[0075] In step S2 and step S3, the first chemical vapor deposition and the second chemical vapor deposition are preferably performed in a fluidized bed reactor.

[0076] In step S3, the carbon source for the second chemical vapor deposition is preferably an organic carbon source.

[0077] The organic carbon source is preferably one or more of acetylene, methane and propylene, such as acetylene.

[0078] The flow rate of the organic carbon source is preferably 80-150 cc / min, for example, 100 cc / min.

[0079] In step S3, the temperature of the second chemical vapor deposition is preferably 500-700°C, for example 600°C.

[0080] In step S3, the time of the second chemical vapor deposition is preferably 2-4 h, for example 2 h.

[0081] In step S3, the atmosphere of the second chemical vapor deposition is preferably an inert atmosphere. The inert atmosphere may be nitrogen or an inert gas (such as argon). The inert atmosphere in the present invention refers to a gas environment that does not chemically react with raw materials or other substances, and is not equivalent to an inert gas, such as nitrogen.

[0082] The flow rate of the atmosphere is preferably 350-450 cc / min, for example 400 cc / min.

[0083] In step S3, the method of removing transition metals is preferably acid washing.

[0084] The acid in the pickling agent of the pickling treatment preferably includes one or more of nitric acid, sulfuric acid and hydrochloric acid, such as nitric acid.

[0085] The concentration of the acid in the pickling reagent of the pickling treatment is preferably 8%-15%, for example, 10%, where the percentage is the percentage of the mass of the acid to the total mass of the pickling reagent.

[0086] The temperature of the pickling treatment is preferably 55-65°C, for example 60°C.

[0087] The pickling treatment time is preferably 2-5 hours, for example 3 hours.

[0088] In step S3, the removal of transition metals preferably includes filtering, washing and drying. Preferably, the washing agent is water.

[0089] The present invention provides a composite silicon-carbon material, which is prepared by the composite silicon-carbon material preparation method as described above.

[0090] In the present invention, the composite silicon-carbon material may be a core-shell structure; the core in the core-shell structure includes porous carbon spheres and silicon nanoparticles, and the silicon nanoparticles are distributed on the surface and in the pores of the porous carbon spheres; the shell in the core-shell structure is a carbon layer, and carbon nanotubes are distributed in the composite silicon-carbon material, and the carbon nanotubes are distributed in one or more of the carbon layer, the surface and pores of the porous carbon spheres.

[0091] In the present invention, the composite silicon-carbon material is preferably a mesoporous material.

[0092] In the present invention, the specific surface area of ​​the composite silicon-carbon material is preferably 2.7-3 m 2 / g, for example, 2.9 m 2 / g or 3m 2 / g.

[0093] In the present invention, the powder resistivity of the composite silicon-carbon material is preferably 0.4-0.7 Ω·m, for example, 0.47 Ω·m or 0.62 Ω·m.

[0094] In the present invention, the silicon loading of the composite silicon-carbon material is preferably 45%-55%, for example 53% or 49%, where the percentage is the percentage of the mass of the silicon nanoparticles to the total mass of the composite silicon-carbon material.

[0095] In the present invention, the carbon content in the composite silicon-carbon material is preferably 45%-55%, for example 47% or 51%, where the percentage is the percentage of the mass of the carbon in the composite silicon-carbon material to the total mass of the composite silicon-carbon material.

[0096] In the present invention, the tap density of the composite silicon-carbon material is preferably 0.90-1.5 g / cm 3 , for example, 0.93 g / cm 3 .

[0097] The present invention provides an application of the composite silicon-carbon material as described above as a negative electrode material in a lithium-ion battery.

[0098] The present invention also provides a lithium ion battery, which comprises the composite silicon-carbon material as described above.

[0099] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0100] The reagents and raw materials used in the present invention are commercially available.

[0101] The positive and progressive effects of the present invention are:

[0102] In the preparation method of the composite silicon-carbon material of the present invention, porous carbon balls are obtained by adopting a carbon ball precursor including polymer nanospheres containing transition metals and a carbon source. The obtained composite silicon-carbon material has a high silicon loading content and excellent stability and conductivity. The lithium-ion battery using the composite silicon-carbon material as the negative electrode material has excellent capacity performance and can take into account excellent cycle performance and first efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0103] Figure 1 Schematic diagram of the structure of the porous carbon spheres obtained in step S1 in Example 1-9.

[0104] Reference numerals:

[0105] Nickel coating 1

[0106] Hole 2

[0107] Porous carbon sphere matrix 3 DETAILED DESCRIPTION

[0108] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0109] Example 1

[0110] (1) Preparation of composite silicon-carbon materials:

[0111] S0. Preparation of carbon sphere precursor:

[0112] S0-1, coarsening treatment: Take 50 mL of concentrated sulfuric acid and slowly add it into 10 mL of deionized water, then add 1 g of potassium dichromate and stir evenly, add PS nanospheres (3 g, particle size 200 nm), ultrasonicate at 50 °C for 1 h, centrifuge and wash the PS nanospheres with deionized water.

[0113] S0-2, sensitization treatment: The PS nanospheres obtained by the roughening treatment were dispersed in 10 mL of water, and 10 mL of PdCl2 with a concentration of 3 g / L and SnCl2 with a concentration of 20 mL / L were added. After mixing evenly, ultrasonic treatment was performed at 50°C for 1 h. After the treatment, the polymer nanosphere matrix was obtained by washing with deionized water.

[0114] S0-3, chemical plating method to prepare transition metal-containing polymer nanospheres: 3g of the above-mentioned polymer nanosphere matrix treated with sensitization was poured into 100 mL of chemical plating solution, ultrasonicated at 40 °C for 1 h, centrifuged after completion, repeatedly washed with deionized water, and dried at 50 °C to obtain transition metal-containing polymer nanospheres (including polymer nanosphere matrix and nickel coating layer, with a particle size of 200 nm). The preparation method of the chemical plating solution includes the following steps: first, 4g NiSO4·6H2O was added to deionized water; then 6g NaH2PO2 was added; then 6g Na3C6H5O7·2H2O was added; finally, 3g NH4Cl was added, dissolved completely, sodium hydroxide (10% mass fraction) was added, and the pH was adjusted to 8.

[0115] S0-4, preparation of carbon sphere precursor: Take 60 g of phenolic resin with a softening point of 95~105℃, dissolve it with 90 g of ethanol, add 3.6 g of hexamethylenetetramine curing agent, and then add 3 g of transition metal-containing polymer nanospheres, mix well to obtain a carbon sphere precursor mixture. Prepare 600 g of PVA aqueous solution with a mass fraction of 1.4%, pour the carbon sphere precursor mixture into it while stirring at a speed of 400r / min, react at 115℃ for 1 h, filter and dry after curing, and finally obtain a carbon sphere precursor.

[0116] S1. Preparation of porous carbon spheres:

[0117] S1-1, heat-treating the carbon sphere precursor in a nitrogen atmosphere: heating to 300°C at a heating rate of 5°C / min and staying there for 2 h;

[0118] S1-2, then carbonization treatment: in a nitrogen atmosphere, heating to 800°C at a heating rate of 2°C / min and staying for 2 h;

[0119] S1-3. Perform activation treatment again: raise the temperature to 950°C at a heating rate of 1°C / min, replace nitrogen with carbon dioxide, and activate with carbon dioxide for 3 h to obtain porous carbon spheres.

[0120] The structural diagram of the porous carbon sphere is shown in Figure 1 The porous carbon sphere comprises a porous carbon sphere matrix 3, a nickel coating layer 1 and pores 2.

[0121] S2. Preparation of silicon-carbon material precursor:

[0122] The prepared porous carbon spheres were added into a fluidized bed reactor, and nitrogen was introduced to replace the air in the reactor. Nitrogen was used as the protective gas, and the fluidized bed was heated to 600°C at a heating rate of 3°C / min. A mixed gas of nitrogen (flow rate of 500cc / min) and silane (SiH4, flow rate of 250cc / min) was introduced, and the deposition time was 3 hours to obtain a silicon-carbon material precursor.

[0123] S3. Preparation of composite silicon-carbon material:

[0124] S3-1. Then, the obtained silicon-carbon material precursor is subjected to a second chemical vapor deposition: the silane gas is replaced with acetylene gas, and the gas is ventilated at 600° C. for 2 hours at a flow rate of 400 cc / min of nitrogen gas and 100 cc / min of acetylene gas.

[0125] S3-2. Removal of transition metals: After the material is cooled, take it out and soak it in 10% nitric acid at 60°C for 3 hours to wash away the nickel metal. Then filter the material and wash it with deionized water to obtain the final composite silicon-carbon material.

[0126] (2) Preparation of button-type lithium-ion batteries

[0127] According to the mass ratio of composite silicon-carbon material, conductive agent Super P (SP), carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) being 90:4:2:4 (100 parts by mass in total), binder CMC, SBR, conductive agent SP and solvent ethanol (220 mL) were added to the composite silicon-carbon material respectively, mixed evenly, and prepared into negative electrode slurry. The negative electrode slurry was coated on copper foil and vacuum dried for 12 hours to prepare a negative electrode sheet. LiPF6 / EC+DEC was used as the electrolyte, and the volume ratio of EC and DEC was 1:1. A metal lithium sheet was used as the counter electrode, and polyethylene PE was used as the separator. The negative electrode sheet, separator, metal lithium sheet and electrolyte were assembled in a glove box filled with hydrogen to obtain a button lithium-ion battery.

[0128] Example 2

[0129] The difference between this embodiment and embodiment 1 is that in step S0-3, the pH of the chemical plating solution is 9, and the other conditions are consistent with those in embodiment 1.

[0130] Example 3

[0131] The difference between this embodiment and embodiment 1 is that in step S0-3, the pH of the chemical plating solution is 10, and the other conditions are consistent with those in embodiment 1.

[0132] Example 4

[0133] The difference between this embodiment and embodiment 1 is that in step S0-1, polyethylene nanospheres are used to replace PS nanospheres, and the other conditions are consistent with those in embodiment 1.

[0134] Example 5

[0135] The difference between this embodiment and embodiment 1 is that in step S1-1, the heat treatment temperature is 250°C, and the other conditions are consistent with embodiment 1.

[0136] Example 6

[0137] The difference between this embodiment and embodiment 1 is that in step S1-2, the temperature of the carbonization treatment is 750°C, and the other conditions are consistent with those in embodiment 1.

[0138] Example 7

[0139] The difference between this embodiment and embodiment 1 is that in step S1-2, the temperature of the carbonization treatment is 850°C, and the other conditions are consistent with those in embodiment 1.

[0140] Example 8

[0141] The difference between this embodiment and embodiment 1 is that in step S1-2, the temperature of the carbonization treatment is 900°C, and the other conditions are consistent with those in embodiment 1.

[0142] Example 9

[0143] The difference between this embodiment and embodiment 1 is that in step S1-3, the temperature of the activation treatment is 1000°C, and the other conditions are consistent with those in embodiment 1.

[0144] Comparative Example 1

[0145] The difference between this comparative example and Example 1 is that there is no step S0-3, and in step S0-4, the polymer nanosphere matrix is ​​used to replace the polymer nanosphere containing transition metal; that is, in step S1, the obtained carbon sphere precursor only includes the polymer nanosphere matrix, but does not include the nickel coating layer, and the other conditions are consistent with Example 1.

[0146] Comparative Example 2

[0147] The difference between this comparative example and Example 1 is that steps S0-1, S0-2 and S0-3 are omitted, and polymer nanospheres containing transition metals are not added in step S0-4; that is, in step S1, the obtained carbon sphere precursor does not include polymer nanospheres containing transition metals, and the other conditions remain consistent with Example 1.

[0148] Comparative Example 3

[0149] The difference between this comparative example and Example 1 is that step S1-1 is omitted, that is, no heat treatment is performed, and the other conditions are the same as those in Example 1.

[0150] Effect Example 1

[0151] The porous carbon spheres obtained in Examples 1-9 and Comparative Examples 1-3 were tested for Dv50 particle size, pore volume, specific surface area and element content, and the test results are shown in Table 1. The particle size was tested using a laser particle size analyzer, the pore volume and specific surface area were tested using a gas adsorption BET method, and the element content was tested using EDS.

[0152] Effect Example 2

[0153] The silicon loading, powder resistivity, specific surface area and tap density of the composite silicon-carbon materials obtained in Examples 1-9 and Comparative Examples 1-3 were tested respectively. The silicon loading was tested using a TGA thermogravimetric analyzer, the powder resistivity was tested using an RTS-4 four-probe tester, the specific surface area was tested using a gas adsorption BET method, and the tap density was tested using a tap density analyzer (Dandong Better BT-311). The above test results are shown in Table 2.

[0154] Effect Example 3

[0155] The button-type lithium-ion batteries prepared in Examples 1-9 and Comparative Examples 1-3 were tested for the first discharge capacity, first efficiency and cycle performance. The test was carried out in a Wuhan Landian Xinwei 5v / 10mA battery tester, with the charge and discharge voltage range controlled at 0.005-2.0V, the charge and discharge rate at 0.5C, and the charge and discharge cycle was carried out. The capacity retention rate of 150 cycles, 300 cycles and 400 cycles was tested in turn. Specific test data are shown in Tables 3 and 4.

[0156]

[0157]

[0158]

[0159]

[0160] According to Table 1, Table 2, Table 3 and Table 4, the specific surface area of ​​the porous carbon spheres obtained in Examples 1-9 of the present invention can reach 1523-1823 m 2 / g, Dv50 particle size can reach 9.8-11.1μm, pore volume can reach 0.74-0.95 cm 3 / g, the proportion of micropores can reach 58%-74%, the proportion of mesopores can reach 20%-32%, the proportion of macropores can reach 6%-10%, the content of carbon element can reach 88.6%-94%, the content of oxygen element can reach 1.2%-7.7%, and the content of nickel element can reach 1.5%-5.4%; the specific surface area of ​​the obtained composite silicon-carbon material can reach 2.6-4 m 2 / g, the powder resistivity can reach 0.41-0.87 Ω·m, the silicon loading can reach 43%-54%, and the tap density can reach 0.92-0.98 g / cm 3 . The lithium-ion battery containing the composite silicon-carbon material has excellent capacity performance, and can take into account excellent first-time efficiency and cycle performance. Specifically, the first discharge capacity of the lithium-ion battery can reach 1810 mAh / g, or even more than 1900 mAh / g; the first efficiency can reach more than 89%, or even more than 93%; the cycle capacity retention rate after 400 cycles can reach more than 85%.

[0161] The inventors have found that the composite silicon-carbon material of the present invention has a higher silicon loading and a lower powder resistivity, and the lithium-ion battery containing it has excellent capacity performance, and can take into account excellent initial efficiency and cycle performance. However, the lithium-ion battery obtained by using a polymer nanosphere matrix, not using transition metal-containing polymer nanospheres or not performing heat treatment, cannot achieve the above-mentioned excellent electrochemical performance. This may be because the pore structure brought about by using PS as a template, the resulting composite silicon-carbon material has a larger pore volume, so that it can load more silicon, and at the same time has a larger space for buffering silicon expansion. During the deposition process, compared with no nickel doping, the addition of nickel metal can well promote the deposition of silane and the growth of carbon nanotubes.

[0162] Compared with Example 1, the comparative example 1 uses a polymer nanosphere matrix, that is, in step S1, the obtained carbon sphere precursor only includes the polymer nanosphere matrix, but does not include the nickel coating layer. When the obtained composite silicon-carbon material is applied to a lithium ion battery, the first discharge capacity of the obtained lithium ion battery is significantly reduced, and the first efficiency and the cycle capacity retention rate after 400 cycles are also poor.

[0163] Compared with Example 1, Comparative Example 2 does not use transition metal-containing polymer nanospheres, that is, in step S1, the obtained carbon sphere precursor does not include transition metal-containing polymer nanospheres. When the obtained composite silicon-carbon material is applied to a lithium-ion battery, the first discharge capacity, first efficiency and cycle capacity retention rate after 400 cycles of the obtained lithium-ion battery are significantly deteriorated.

[0164] Compared with Example 1, in Comparative Example 3, step S1-1 is omitted, i.e., heat treatment is not performed, but step S1-2, i.e., carbonization treatment, is performed directly. The initial discharge capacity, initial efficiency, and cycle capacity retention rate of the obtained lithium-ion battery after 400 cycles are significantly deteriorated.

[0165] Comparing Examples 1, 2 and 3, it can be seen that as the pH value of the chemical plating solution increases successively, the silicon loading of the obtained composite silicon-carbon material decreases successively, and the powder resistivity increases successively. The first discharge capacity and the first efficiency of the obtained lithium-ion battery both decrease successively. This may be because controlling the pH value can control the doping amount of nickel metal, and the presence of nickel metal can catalyze the deposition of silane, thereby affecting the conversion rate of silane and the loading amount of silicon.

[0166] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.

Claims

1. A method for preparing a composite silicon-carbon material, characterized in that: It includes the following steps: S1, heat-treating, carbonizing and activating a carbon sphere precursor to obtain porous carbon spheres; the carbon sphere precursor comprises a carbon source and a transition metal-containing polymer nanosphere; the transition metal-containing polymer nanosphere comprises a polymer nanosphere matrix and a transition metal coating layer; S2, depositing silicon on the porous carbon spheres using a first chemical vapor deposition method to obtain a silicon-carbon material precursor; S3, depositing carbon on the silicon-carbon material precursor using a second chemical vapor deposition method; The transition metal is removed to obtain a composite silicon-carbon material.

2. The method for preparing the composite silicon-carbon material according to claim 1, characterized in that: In step S1, the carbon sphere precursor satisfies one or more of the following conditions ac: a. In step S1, the polymer nanosphere matrix is ​​polyethylene nanosphere and / or polystyrene nanosphere; b. In step S1, the transition metal in the transition metal coating layer includes one or more of nickel, copper, tin, palladium and iron, preferably one or more of nickel, tin and palladium; c. In step S1, the preparation method of the transition metal-containing polymer nanospheres is a chemical plating method; the chemical plating method preferably comprises the following steps: mixing the polymer nanosphere matrix and the transition metal plating solution, centrifuging, washing, and drying to obtain; Wherein, the pH value of the transition metal plating solution is preferably 6-10, for example 8 or 9; Wherein, the particle size of the polymer nanosphere matrix is ​​preferably 20-200 nm, for example, 200 nm.

3. The method for preparing the composite silicon-carbon material according to claim 1, characterized in that: In step S1, the carbon source is phenolic resin; the softening point of the phenolic resin is preferably 95-105°C; Preferably, the method for preparing the carbon sphere precursor comprises the following steps: S0, adding a carbon sphere precursor mixture into a dispersant aqueous solution, and subjecting the mixture to a curing reaction to obtain a carbon sphere precursor; wherein the carbon sphere precursor mixture comprises a phenolic resin, a curing agent, a solvent, and polymer nanospheres containing transition metals; Wherein, the curing agent is preferably one or more of hexamethylenetetramine, polyoxymethylene, A-stage thermosetting phenolic resin and aniline; Wherein, the mass ratio of the phenolic resin to the curing agent is preferably (15-20):1, for example, 16.7:1; Wherein, the mass ratio of the phenolic resin and the transition metal-containing polymer nanospheres is preferably (20-40): 1; The curing reaction temperature is preferably 95-130°C, for example 115°C; preferably, the curing reaction time is 1-2h; Preferably, the adding is performed while stirring; the stirring speed is preferably 300-500 r / min, for example 400 r / min; Wherein, the dispersant in the dispersant aqueous solution is preferably one or more of polyvinyl alcohol, polyvinyl pyrrolidone, polyethylene glycol and sodium dodecyl sulfate, for example, polyvinyl alcohol; The mass fraction of the dispersant aqueous solution is preferably 0.8%-2%, for example 1.4%, where the percentage is the mass percentage of the dispersant in the dispersant aqueous solution to the mass percentage of the dispersant aqueous solution.

4. The method for preparing the composite silicon-carbon material according to claim 1, characterized in that: Step S1 satisfies one or more of the following conditions ah: a. In step S1, the temperature of the heat treatment is 200-400°C, preferably 250-350°C, more preferably 280-320°C, for example 300°C; b. In step S1, the heat treatment time is 1-3 h, for example, 2 h; c. In step S1, the heating rate to the heat treatment temperature is 1-5°C / min, for example, 5°C / min; d. In step S1, the temperature of the carbonization treatment is 700-900°C, preferably 750-850°C, for example 800°C; e. In step S1, the carbonization treatment time is 2-4 hours, for example, 2 hours; f. In step S1, the heating rate to the temperature of the carbonization treatment is 1-5°C / min, for example, 2°C / min; g. In step S1, the atmosphere of the carbonization treatment is an inert atmosphere; h. In step S1, the activation treatment is alkali activation or gas activation; wherein the gas activation is preferably carbon dioxide activation or water vapor activation; The activation temperature of carbon dioxide is preferably 850-1000°C, further preferably 900-1000°C, and more preferably 900-950°C; the heating rate to the activation temperature of carbon dioxide is preferably 1-5°C / min, for example 1°C / min; The activation time of carbon dioxide is preferably 2-6 h, for example 3 h.

5. The method for preparing the composite silicon-carbon material according to claim 1, characterized in that: In step S1, the porous carbon spheres satisfy one or more of the following conditions ai: a. In step S1, the specific surface area of ​​the porous carbon sphere is 1500-2500 m 2 / g, for example, 1523 m 2 / g, 1532 m 2 / g, 1583 m 2 / g, 1624 m 2 / g, 1625 m 2 / g, 1642 m 2 / g, 1682 m 2 / g, 1683 m 2 / g or 1823 m 2 / g; b. In step S1, the Dv50 particle size of the porous carbon sphere is 9-12 μm, for example, 9.8 μm, 10.3 μm, 10.4 μm, 10.5 μm, 10.7 μm, 10.8 μm or 11.1 μm; c. In step S1, the pore volume of the porous carbon sphere is 0.6-1.0 cm 3 / g, preferably 0.7-0.95 cm 3 / g, for example, 0.74 cm 3 / g, 0.79 cm 3 / g, 0.81 cm 3 / g, 0.83 cm 3 / g, 0.84 cm 3 / g, 0.85 cm 3 / g or 0.86 cm 3 / g; d. In step S1, the proportion of micropores in the porous carbon sphere is 58%-98%, preferably 58%-74%, for example, 64%, 66%, 67%, 68% or 70%, where the percentage is the proportion of the volume of the micropores to the total pore volume of the porous carbon sphere; e. In step S1, the proportion of mesopores in the porous carbon sphere is 10%-32%, preferably 20%-30%, for example, 24%, 25%, 26%, 27% or 29%, where the percentage is the proportion of the volume of the mesopores to the total pore volume of the porous carbon sphere; f. In step S1, the proportion of macropores in the porous carbon sphere is 1%-15%, for example, 6%, 7%, 8%, 9% or 10%, where the percentage is the proportion of the volume of the macropores to the total pore volume of the porous carbon sphere; g. In step S1, the carbon content of the porous carbon sphere is 85%-94%, preferably 88%-92%, and the carbon content of the porous carbon sphere is, for example, 88.6%, 90.3%, 90.8%, 91.6%, 92.4%, 92.9%, 93.3% or 93.6%, where the percentage is the mass percentage of the total mass of the porous carbon sphere; h. In step S1, the content of oxygen in the porous carbon sphere is 1%-8%, preferably 3%-6%, and the content of oxygen in the porous carbon sphere is, for example, 1.2%, 1.8%, 2.8%, 4.1%, 4.2%, 4.3%, 4.7%, 4.8% or 7.7%, where the percentage is the mass percentage of the total mass of the porous carbon sphere; i. In step S1, the content of transition metal elements in the porous carbon sphere is 1%-6%, where the percentage is the mass percentage of the total mass of the porous carbon sphere; Among them, when the transition metal element in the porous carbon sphere includes nickel, the nickel content is preferably 1.5%-5.5%, for example, 2.8%, 3.5%, 4.2%, 4.3%, 4.8%, 5.2%, 5.3% or 5.4%, where the percentage is the mass percentage of the total mass of the porous carbon sphere.

6. The method for preparing the composite silicon-carbon material according to claim 1, characterized in that: Step S2 and step S3 satisfy one or more of the following conditions ak: a. In step S2, the silicon source of the first chemical vapor deposition is an organic silane, more preferably one or more of methylsilane, disilane and chlorosilane, for example, methylsilane; wherein the flow rate of the silicon source is preferably 200-300 cc / min, for example, 250 cc / min; b. In step S2, the temperature of the first chemical vapor deposition is 500-700° C., for example, 600° C.; c. In step S2, the first chemical vapor deposition time is 2-6 h, for example, 3 h; d. In step S2, the heating rate of heating to the temperature of the first chemical vapor deposition is 1-5°C / min, for example, 3°C / min; e. In step S2, the atmosphere of the first chemical vapor deposition is an inert atmosphere; wherein the flow rate of the atmosphere is preferably 450-550 cc / min, for example, 500 cc / min; f. In step S2 and step S3, the first chemical vapor deposition and the second chemical vapor deposition are performed in a fluidized bed reactor; g. In step S3, the carbon source for the second chemical vapor deposition is an organic carbon source, and the organic carbon source is preferably one or more of acetylene, methane and propylene, such as acetylene; wherein the flow rate of the organic carbon source is preferably 80-150 cc / min, such as 100 cc / min; h. In step S3, the temperature of the second chemical vapor deposition is 500-700° C., for example, 600° C.; i. In step S3, the second chemical vapor deposition time is 2-4 h, for example, 2 h; j. In step S3, the atmosphere of the second chemical vapor deposition is an inert atmosphere; wherein the flow rate of the atmosphere is preferably 350-450 cc / min, for example, 400 cc / min; k. In step S3, the method of removing transition metals is pickling treatment.

7. A composite silicon-carbon material, characterized in that: The composite silicon-carbon material is prepared by the method for preparing the composite silicon-carbon material according to any one of claims 1 to 6.

8. The composite silicon-carbon material according to claim 7, characterized in that: The composite silicon-carbon material satisfies one or more of the following conditions: a. The composite silicon-carbon material is a mesoporous material; b. The composite silicon-carbon material is a core-shell structure; the core of the core-shell structure includes porous carbon spheres and silicon nanoparticles, and the silicon nanoparticles are distributed on the surface and in the pores of the porous carbon spheres; the shell of the core-shell structure is a carbon layer, and carbon nanotubes are distributed in the composite silicon-carbon material, and the carbon nanotubes are distributed in one or more of the carbon layer, the surface and the pores of the porous carbon spheres; c. The specific surface area of ​​the composite silicon-carbon material is 2.7-3 m 2 / g, for example, 2.9 m 2 / g or 3 m 2 / g; d. The powder resistivity of the composite silicon-carbon material is 0.4-0.7 Ω·m, for example, 0.47 Ω·m or 0.62 Ω·m; e. The silicon loading of the composite silicon-carbon material is 45%-55%, for example, 53% or 49%, where the percentage is the percentage of the mass of the silicon nanoparticles to the total mass of the composite silicon-carbon material; f. The carbon content in the composite silicon-carbon material is 45%-55%, for example, 47% or 51%, where the percentage is the percentage of the mass of the carbon in the composite silicon-carbon material to the total mass of the composite silicon-carbon material; g, the tap density of the composite silicon-carbon material is preferably 0.90-1.5 g / cm 3 , for example, 0.93 g / cm 3 .

9. Use of the composite silicon-carbon material as claimed in claim 7 or 8 as a negative electrode material in a lithium-ion battery.

10. A lithium ion battery, characterized in that: It comprises the composite silicon-carbon material as claimed in claim 7 or 8.

Citation Information

Patent Citations

  • Preparation method of lithium ion battery negative electrode material and product thereof

    CN101585528A

  • Three-dimensional connected curved graphene and preparation method thereof as well as electrode, capacitor and lithium battery

    CN103833031A

  • Nano silicon-carbon composite material for secondary lithium battery as well as preparation method and application of nano silicon-carbon composite material

    CN115020689A

  • Silicon-carbon negative electrode material, preparation method thereof, battery and application

    CN117254011A

  • Spherical porous silicon-carbon composite material as well as preparation method and application thereof

    CN118495501A

Cited By

  • Spherical porous carbon as well as preparation method and application thereof

    CN119976806A

  • Silicon-carbon composite material, preparation method thereof, negative electrode, solid-state battery and electric device

    CN122822727A